Managing Cow’s Milk Protein Allergy in Indonesia: A Cost-effectiveness Analysis of Hypoallergenic Milk Formulas from the Private Payers’ Perspective - Ana Teresa Paquete; Rui Martins; Mark P. Connolly; Badriul Hegar; Zakiudin Munasir; Stephanus Stephanus (Journal of Health Economics and Outcomes Research)
**Background:** Cow’s milk protein allergy is very common in early childhood. Extensively hydrolyzed formulas are recommended in the first-line management of cow’s milk protein allergy in non-breastfed children. Choice of formulas should be informed by efficacy and cost data. **Objectives:** This study aims to compare the cost-effectiveness of extensively hydrolyzed casein formula with _Lacticaseibacillus rhamnosus_ Gorbach Goldin (EHCF+LGG), extensively hydrolyzed whey formula (EHWF), amino acid formula, and soy formula in the first-line management of cow’s milk protein allergy in non-breastfed children in Indonesia. **Methods:** A trial-based decision analytic cohort model was adapted to simulate the occurrence of cow’s milk protein allergy symptoms or being symptom free. The model was based on a prospective nonrandomized study that followed up children for 36 months. Costs and health consequences were discounted at 3% annually. Resources required to manage cow’s milk protein allergy and unit costs for clinical appointments and exams were based on a panel of 15 clinicians, from a private payers’ perspective. Other unit costs were based on publicly available national data. Results were reported as cost per additional child free from allergic manifestations or per additional immunotolerant child at 3 years, and per life-years under the same conditions. Uncertainty was assessed using deterministic and probabilistic sensitivity analysis. **Results:** Children receiving EHCF+LGG were associated with more symptom-free time, a higher probability of cow’s milk tolerance at 3 years, and lower healthcare resources and transportation use when compared with children receiving other formulas (with 38%-49% lower costs). Formula costs were lower for soy, but EHCF+LGG was predicted to save 9% and 54% of overall costs compared with extensively hydrolyzed whey formula and amino acid formula, respectively. Results were robust to sensitivity analyses. **Conclusion:** Use of EHCF+LGG resulted in more symptom-free time and the highest 3-year probability of cow’s milk tolerance. It also led to healthcare resource and transportation savings when compared with other hypoallergenic milk formulas. Soy formula remained an alternative if formula price represents a major constraint.